2005
DOI: 10.1093/pch/10.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a black hole: Transition from paediatric to adult care services for youth with diabetes

Abstract: During the passage from adolescence to adulthood, individuals are expected to go through three psychological stages: identity formation (finding out who they are), intimacy (establishment of stable intimate relationships) and generativity (productive lifestyle, career or vocational realization). Having diabetes may complicate this process. Further, the period of late adolescence and early adulthood coincides with the transition of care from paediatric to adult care services. This transition is a time when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…In general, when there is no formal transition program in place, a "loss to follow-up" rate of > 20-25% can be expected in the 2-4 years after discharge from the pediatric center. [6][7][8][9][10][11][12] One study from Finland showed a significant improvement in metabolic control after transition to adult care, although other studies have failed to confirm this. 6 Of note, in a recent health services study of 1,507 adolescents with diabetes undergoing a transition of care at 18 years of age in the Province of Ontario, Canada, we reported two important findings: there was a small but significant increased risk of hospitalization for Adolescents leaving their pediatric team and starting afresh with a new physician and new team were more likely to be hospitalized for DKA than those whose adult team included some of the members of their pediatric team.…”
Section: Studies Of Transition Outcomesmentioning
confidence: 99%
“…In general, when there is no formal transition program in place, a "loss to follow-up" rate of > 20-25% can be expected in the 2-4 years after discharge from the pediatric center. [6][7][8][9][10][11][12] One study from Finland showed a significant improvement in metabolic control after transition to adult care, although other studies have failed to confirm this. 6 Of note, in a recent health services study of 1,507 adolescents with diabetes undergoing a transition of care at 18 years of age in the Province of Ontario, Canada, we reported two important findings: there was a small but significant increased risk of hospitalization for Adolescents leaving their pediatric team and starting afresh with a new physician and new team were more likely to be hospitalized for DKA than those whose adult team included some of the members of their pediatric team.…”
Section: Studies Of Transition Outcomesmentioning
confidence: 99%
“…As a consequence, the concept of transition emerged, defined as a process of "a purposeful planned movement of adolescents and young adults with chronic physical and medical conditions from child-centered to adult-orientated health care systems" [3]. Unfortunately, the transfer to AHC is still often the result of an ad hoc decision, and some adolescents even drop out of the health care system temporarily until they seek help for acute medical problems in the AHC system [17,18,23,30,32]. Such poor transition processes may have significant negative effects on morbidity and mortality in young adults [2,10,17].…”
Section: Ahc Adult Health Carementioning
confidence: 99%
“…Young adults with diabetes, as with any teenage child facing a chronic long term condition, are more vulnerable to the changes of adaptation in care and hence there is greater risk of this care being compromised at a time where they need it most and at a time where the longer term complications (as well as acute) need to be screened and monitored for [32] . One key obstacle identified here is the loss to follow up of these patients.…”
mentioning
confidence: 99%